AGAMA DAN SEKULERISME Kematian Sekulerisme Dalam Perspektif Aksi Bela Islam - Ginanjar Kartasasmita (UIN Sunan Gunung Djati Bandung, 2017)
This article will discuss about the real phenomenon that occurred in the Islamic community in Indonesia, the act of defending Islam became a symbol of the emergence of the spirit of Islamization that is sweeping this nation, the Islamic belief to break the movement of secularism that swept many countries with the majority of the population of Islam in a few years, but the Islamic defenses show that Islamic society in Indonesia has risen